Pengaruh Supervisi Akademik Kepala Sekolah, Motivasi dan Komitmen Guru terhadap Kinerja Guru MA di Aceh Tengah: The Influence of Principals' Academic Supervision, Teacher Motivation, and Teacher Commitment on the Performance of MA Teachers in Central Aceh - Zahrayani Zahrayani; Sony Muhammad Ikhsan Mangkuwinata; Iskandar Iskandar (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Teacher performance is a primary determinant of instructional quality in madrasahs (Islamic senior high schools); however, its achievement is often influenced by various managerial and psychological factors that have not been fully confirmed in specific local contexts. This study aims to analyze the influence of the principal's academic supervision, teacher work motivation, and teacher work commitment on the performance of Madrasah Aliyah (MA) teachers in Central Aceh Regency, both partially and simultaneously. The study employs a quantitative approach using an explanatory survey method. The sample consists of 120 teachers from eight *Madrasah Aliyah* institutions (three state and five private schools), selected via proportional random sampling. Data were collected using a five-point Likert scale questionnaire—validated through factor analysis and proven reliable with Cronbach's Alpha values exceeding 0.60—and subsequently analyzed using multiple linear regression with SPSS 25.0 software. The results indicate that, when analyzed individually, teacher work motivation has a positive and significant effect on teacher performance (t = 2.052; Sig. = 0.046 < 0.05), whereas the principal's academic supervision (t = 0.399; Sig. = 0.379) and teacher work commitment (t = 0.505; Sig. = 0.168) do not have a significant partial effect. Simultaneously, the three independent variables significantly influence teacher performance (F = 8.234; Sig. = 0.000 < 0.05), contributing 38.1% to the variance (R² = 0.381), while factors outside the model explain the remaining 61.9%. These findings indicate that work motivation is the most dominant factor in driving teacher performance. In contrast, the effectiveness of academic supervision implementation and the strengthening of teacher work commitment require substantial improvement to yield a tangible impact on performance enhancement.